Sensitive Quantification of Cell-Free Tumor DNA for Early Detection of Recurrence in Colorectal Cancer - Stasik, Sebastian; Mende, Marika; Schuster, Caroline; Mahler, Sandra; Aust, Daniela; Tannapfel, Andrea; Reinacher-Schick, Anke; Baretton, Gustavo; Krippendorf, Claudia; Bornhäuser, Martin; Ehninger, Gerhard; Folprecht, Gunnar; et al. (Frontiers in Genetics, 2022)
The detection of plasma cell-free tumor DNA (ctDNA) is prognostic in colorectal cancer (CRC) and has potential for early prediction of disease recurrence. In clinical routine, ctDNA-based diagnostics are limited by the low concentration of ctDNA and error rates of standard Next-Generation Sequencing (NGS) approaches. We evaluated the potential to increase stability and yield of plasma cell-free DNA (cfDNA) for routine diagnostic purposes using different blood collection tubes and various manual or automated cfDNA extraction protocols. Sensitivity for low-level ctDNA was measured in KRAS-mutant cfDNA using an error-reduced NGS procedure. To test the applicability for rapid evaluation of ctDNA persistence in clinical routine, we prospectively analyzed postoperative samples of 67 CRC (stage II) patients. ctDNA detection was linear between 0.0045-45%, with high sensitivity (94%) and specificity (100%) for mutations at 0.1% VAF. Stability and yield of cfDNA were superior using Streck BCT tubes and a protocol by Zymo Research. Sensitivity for ctDNA increased 1.5-fold by the integration of variant reads from triplicate PCR reactions and with PCR template concentration. In clinical samples, ctDNA persistence was found in 9% of samples, drawn two weeks after surgery. Moreover, in a retrospective analysis of 14 CRC patients with relapse during adjuvant therapy, we successfully detected ctDNA (median 0.38% VAF; range 0.18-5.04% VAF) in 92.85% of patients significantly prior (median 112 days) to imaging-based surveillance. Using optimized pre-analytical conditions, the detection of postoperative ctDNA is feasible with excellent sensitivity and allows the prediction of CRC recurrence in routine oncology testing.